2007
DOI: 10.1016/j.jnutbio.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary isoflavones differentially induce gene expression changes in lymphocytes from postmenopausal women who form equol as compared with those who do not

Abstract: Human and animal studies suggest that dietary soy isoflavones reduce cancer risk, ameliorate postmenopausal syndrome and decrease bone resorption in postmenopausal women. The capacity to form the metabolite equol from daidzein is suggested as an important modulator of response to isoflavones; this capacity depends on gut colonization with appropriate bacteria. We administered a dietary supplement containing high-dose purified soy isoflavones (genistein, 558 mg/day; daidzein, 296 mg/day; and glycitein, 44 mg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 78 publications
1
50
3
Order By: Relevance
“…A recent attempt in this area associated circulation levels of a single microbial polyphenol metabolite with differences in long-term bioactivity as defined by transcriptomics of leukocytes (111). We envisage that the introduction of nutrikinetic phenotypes will allow for stronger associations between nutritional phenotypes and bioactivity of polyphenols.…”
Section: Bioavailability-bioactivity Relationsmentioning
confidence: 98%
“…A recent attempt in this area associated circulation levels of a single microbial polyphenol metabolite with differences in long-term bioactivity as defined by transcriptomics of leukocytes (111). We envisage that the introduction of nutrikinetic phenotypes will allow for stronger associations between nutritional phenotypes and bioactivity of polyphenols.…”
Section: Bioavailability-bioactivity Relationsmentioning
confidence: 98%
“…To determine the selectivity of the genes regulated by S-equol, gene profiling of genes that contain oestrogenresponse elements was carried out in lymphocytes isolated from postmenopausal women who were either equol producers or not [90]. In the equol producers, oestrogenrelated receptor beta and four orphan nuclear receptors (BROB2, NR2C1, NR2F2 and NR113) were the most overexpressed genes which demonstrating status as an equol producer is associated with selective changes in gene expression [90].…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
“…Another important issue is that rats are known to be equol producers (Setchell et al, 2005), while this is only the case for 20-30% of Western populations (Setchell & Clerici, 2010). In previous studies, differences in gene expression were observed between equol-producers and non-producers (Niculescu et al, 2007;van der Velpen et al, 2014), which also applies to estrogen responsive genes (7.0% in producers, 4.4% in nonproducers). However, this difference is not always addressed in extrapolation of findings from isoflavone animal studies to humans.…”
Section: Discussionmentioning
confidence: 99%